Adherence to Targeted Oral Anticancer Medications - GEYNISMAN, DANIEL M. (Discov Med, 2013)
The use of targeted oral anticancer medications (OAMs) is becoming increasingly prevalent in cancer care. Approximately 25–30% of the oncology drug pipeline involves oral agents and there are now over 50 OAMs approved by the Food and Drug Administration. This change represents a major shift in management of patients with cancer from directly observed, intermittent intravenous therapy to self-administered, oral chronic therapy. The increased prevalence of OAMs raises the issue of adherence in oncology, including understanding the challenges of adherence to OAMs. This review focuses on studies of adherence for patients taking molecularly targeted OAMs for breast cancer, chronic myelogenous leukemia (CML), gastrointestinal stromal tumors (GIST), non-small cell lung cancer (NSCLC), and renal cell carcinoma (RCC). We then discuss barriers to adherence and studies performed to date testing interventions for improving adherence. Finally, we discuss future areas of investigation needed to define and improve adherence to OAMs in targeted therapy for cancer.